Effects of Bezafibrate on Outcome and Pruritus in Primary Biliary Cholangitis With Suboptimal Ursodeoxycholic Acid Response. (January 2018) - Reig, Anna; Sesé, Pilar; Parés, Albert
Abstract : OBJECTIVES: Adding fibrates improves liver biochemistries in patients with primary biliary cholangitis (PBC) and suboptimal response to ursodeoxycholic acid (UDCA). As there are no consistent data regarding the course and outcome, we have assessed the effects of the combined treatment with UDCA and bezafibrate on a long‐term basis. METHODS: A total of 48 patients (45 female) with PBC treated with UDCA and alkaline phosphatase (ALP) above 1.5 times upper normal levels (× UNL) were treated with bezafibrate (400 mg/day) plus UDCA (13–16 mg/kg/day). Changes in clinical features, liver biochemistries, and prognosis after therapy were assessed, as well as pruritus, using a visual analog scale (43 patients) and the 5‐D descriptive pruritus scale. RESULTS: After a median of 38 months, 26 patients (54%) had normalized ALP. In these patients, jaundice, pruritus, and liver stiffness was lower, and age was higher than in patients who remained with elevated ALP. Biochemical improvement was less prominent in patients without ALP normalization. Five of these patients (23%) developed events of disease progression: 1 died, 3 were transplanted, and 1 developed hepatocellular carcinoma. Partial or complete itching relief was reported in all but one case with pruritus. Itching recurrence or worsening was observed after bezafibrate discontinuation. CONCLUSIONS: The long‐term treatment with UDCA and bezafibrate results in excellent response, and is associated with a complete or partial itching relief. Incomplete ALP normalization was observed in patients with advanced disease who remained at risk for developing severe events. The combined treatment is mainly effective in patients with lower fibrosis and severity of cholestasis.